A driving force model for non-strict priority crossing behaviors of right-turn drivers. (January 2016) - Lin, Dianchao; Ma, Wanjing; Li, Li; Wang, Yinhai
Highlights: A micro driving force (MDF) model was developed for right-turn drivers under non-strict priority conditions. The calibration methods and results of calibration of all the parameters used in MDF model based on field data were presented. Model validation results proved the accuracy and reliability of the MDF model. MDF model was extended for the prediction of right-turn vehicle's average crossing speed. The influence of vehicle type, non-motorized traffic flow rate, and non-motorized traffic speed were identified. Abstract: At urban intersections, conflicts between right-turn vehicles and through non-motorized vehicles are a critical cause of traffic congestion and safety challenges. Based on the fact that in different countries there is no strict priority in conflicts between motorized and non-motorized vehicles, this study focused on analysis of the inherent mechanism of this universal phenomenon. By the analogy of a force model for moving vehicles, this paper developed a micro driving force model, including the safety driving force and efficiency driving force, for right-turn drivers which constitute the dominant party during the non-strict priority crossing process. We further demonstrate that the strict priority crossing behavior is a special case of the proposed driving force model. All the parameters used in this model were calibrated through field data collected at twelve signalized intersection sites in Shanghai. Model validation results proved the accuracy and reliability of the proposed driving force model. The model was further proved that it can be used for right-turn vehicle's average crossing speed prediction. The sensitivity analysis identified the influence of vehicle type, non-motorized traffic flow rate, and non-motorized traffic speed on the average speed, and offered support for the rationality of the non-strict priority.